Investigating the Influence of EFL Students’ First Language on the Pronunciation of Long and Short English Vowels - Muhayyang, Maemuna; Sally, Fauzan Hari Sudding; Ramadhani, Adelia; Syahruni, Syahruni (Pascasarjana Universitas Negeri Makassar, 2025)
The impact of an individual's native language on the pronunciation of long and short vowels in English is a common phenomenon, particularly among learners whose first language employs a distinct vowel system. The objective of this study is to gain insight into the manner in which a student's first language affects the pronunciation of long and short English vowels and to identify effective learning strategies employed to overcome the difficulties encountered. This study employed a case study in qualitative method taking eight English Language Education students in 2022/2023 academic year, Universitas Negeri Makassar. To collect the data, semi-structured interview was utilized and analyzed using the framework of qualitative analysis developed by Miles and Huberman Saldana's (2014) theory, which includes data condensation, data presentation, and conclusion drawing/verification. The findings revealed that the lack of differentiation between English long and short vowels in the native language, coupled with difficulties in identifying and articulating vowels, constituted the primary challenges encountered by the students. Nevertheless, several learning strategies were identified to assist in overcoming the difficulties, namely learning from native speakers through online resources, the